Design, synthesis, and anticancer activity of three novel palbociclib derivatives - Li, Tian; Zhou, An-Di; Bai, Li-Fei; Zhang, Xiao-Yang; Zhou, Yu-Ting; Yang, Hai-Li; Xu, Le-Tian; Guo, Xin-Qin; Zhu, Xi-Yu; Wang, Dong-Jin; Gu, Hong-Wei; Wang, Xiao-Ming (Frontiers in Oncology, 2022)
Cancer is one of the most serious diseases threatening human health, so it is particularly important to develop effective tumor-targeting drugs. As the first CDK4/6 inhibitor, palbociclib effectively inhibits tumor proliferation by blocking the cell cycle to the G1 phase. 10-HCPT is a Topo I inhibitor; however, its clinical application has been greatly limited due to its high toxicity. Based on the successful development of double target inhibitors, three novel palbociclib derivatives (HP-1, HP-2, and HP-3) were designed and synthesized from Palbociclib and 10-HCPT, and their biological activities were investigated. At first, the possible binding sites of the three compounds to Topo I and CDK4/6 were predicted by molecular docking. Then, we evaluated the anti-proliferative effects of the three palbociclib derivatives. In general, human lung cancer cells were more sensitive to HP-1, HP-2, and HP-3, especially NCI-H460. In addition, cell cycle arrest and apoptosis induction were investigated by flow cytometry. The three palbociclib derivatives, especially HP-1, had obvious cell cycle arrest phenomenon on NCI-H460 cells and induced apoptosis of NCI-H460 cells significantly. In the end, it was proved that these three drugs had obvious cyclin-dependent kinase inhibitory activities. In short, all the data showed that HP-1, HP-2, and HP-3 could play anti-cancer roles by acting on dual targets and had the characteristics of high efficiencies and low toxicities, which opened up a new idea for the study of palbociclib derivatives.